Peran Psikiatri Dalam Penegakan Hukum Sebagai Visum Et Repertum - Herlin Sobari; Maharani Nurdin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The process of law enforcement and justice is a scientific effort in the settlement of criminal cases on a person's body, health and life such as cases of murder, assault, sexual crimes, acts that cause death or injury, forensic medicine is very much needed, one of which is visum et reertum. Visum Et Repertu itself is a certificate (doctor). Along with the development of legal science, expert testimony in the field of mental health, including psychiatric visum et repertum. Because in everyday life, we are very aware of the needs starting from the requirements of entry in a work, education, and in this case, in particular to handle criminal cases and as evidence in civil matters (for example contract cancellation, forgiveness, grants, divorce and adoption). For criminal cases to date, the most appropriate preparation of expert statements is a criminal case in which a person suspected of having a mental disorder commits violence or someone who has suffered a mental disorder after experiencing physical or psychological abuse.